GRADING SINDROM TEROWONGAN KARPAL BERDASARKAN PEMERIKSAAN LUMBRIKALINTEROSEI - Donny H.Hamid*, Manfaluthy Hakim**,Fitri Octaviana**, Ahmad Yanuar**. (NEURONA, 2011)
INTRODUCTION THE SEVERITY OF CARPAL TUNNEL SYNDROME CTS MAJORITY IS DUE TO LARGE NUMBER OF AVAILABLE TECHNIQUES ELECTROPHYSIOLOGY EXAMINATIO ESPECIALLY THE INTERNAL COMPARISON TO MEDIAN NERVE BEFORE AND AFTER ACROSS THE CARPAL TUNNEL AND COMPARED TO ADJACENT NERVES WHICH NOT ACROSS THE CARPAL TUNNEL AS THE ULNAR OR RADIAL NERVES THE LUMBRICALINTEROSSEI IS A SENSITIVE AND AN EASY MEASUREMENT TECHNIQUE WHICH WILL BE UTILIZED IN GRADING THE SEVERITY OF CTS